Generation and characterization of OX40-ligand fusion protein that agonizes OX40 on T-Lymphocytes - Sato, Ayaka; Nagai, Hodaka; Suzuki, Ayano; Ito, Aya; Matsuyama, Shimpei; Shibui, Nagito; Morita, Masashi; Hikosaka-Kuniishi, Mari; Ishii, Naoto; So, Takanori (Frontiers in Immunology, 2025)
OX40, a member of the tumor necrosis factor (TNF) receptor superfamily, is expressed on the surface of activated T cells. Upon interaction with its cognate ligand, OX40L, OX40 transmits costimulatory signals to antigen-primed T cells, promoting their activation, differentiation, and survival—processes essential for the establishment of adaptive immunity. Although the OX40-OX40L interaction has been extensively studied in the context of disease treatment, developing a substitute for the naturally expressed membrane-bound OX40L, particularly a multimerized OX40L trimers, that effectively regulates OX40-driven T cell responses remains a significant challenge. In this study, we successfully engineered soluble OX40L-fusion proteins capable of robustly activating OX40 on T cells. This was achieved by incorporating functional multimerization domains into the TNF homology domain of OX40L. These OX40L proteins bound to OX40, subsequently activated NF-κB signaling, and induced cytokine production by T cells in vitro. In vivo, mice treated with one of the OX40L-fusion proteins—comprising a single-chain OX40L trimer linked to the C-terminus of the human IgG1 Fc domain, forming a dimer of trimers—exhibited significantly enhanced clonal expansion of antigen-specific CD4+ T cells during the primary phase of the immune response. A comparable antibody-fusion single-chain TNF protein incorporating 4-1BBL, CD70 (CD27L), or GITRL in place of OX40L elicited similar in vivo T cell responses. Thus, we propose that optimizing the multimerization of OX40L proteins through innovative design strategies may facilitate the development of more effective agonists for targeted immunotherapies.